Molecular characterization and gene expression of pattern recognition receptors in brown-marbled grouper (Epinephelus fuscoguttatus) fingerlings responding to vibriosis infection - Mohamed Alipiah, Norfarrah; Salleh, Annas; Sarizan, Nur Maisarah; Ikhsan, Natrah (Elsevier, 2024)
The pathogen recognition system involves receptors and genes that play a crucial role in activating innate immune response in brown-marbled grouper (Epinephelus fuscoguttatus) as a control agent against various infections including vibriosis. Here, we report the molecular cloning of partial open reading frames, sequences characterization, and expression profiles of Pattern Recognition Receptors (PRRs) in brown-marbled grouper. The PRRs, namely pglyrp5, tlr5, ctlD, and ctlE in brown-marbled grouper, possess conserved domains and showed shared evolutionary relationships with other fishes, humans, mammals, birds, reptilians, amphibians, and insects. In infection experiments, up to 50% mortality was found in brown-marbled grouper fingerlings infected with Vibrio alginolyticus compared to 27% mortality infected Vibrio parahaemolyticus and 100% survival of control groups. It is also demonstrated that all four PRRs had higher expression in samples infected with V. alginolyticus compared to V. parahaemolyticus. This PRRs gene expression analysis revealed that all four PRRs expressed rapidly at 4-h post-inoculation even though the Vibrio count was only detected earliest at 12-h post-inoculation in samples. The highest expression recorded was from V. alginolyticus inoculated fish spleen with up to 73-fold change for pglyrp5 gene, followed by 14 to 38-fold expression for the same treatment in spleen, head kidney, and blood samples for other PRRs, namely tlr5, ctlD, and ctlE genes. Meanwhile less than a 10% increase in expression of all four genes was detected in spleen, head kidney, and blood samples inoculated with V. parahaemolyticus. These findings indicated that pglyrp5, tlr5, ctlD, and ctlE play important roles in the early immune response to vibriosis infected, brown-marbled grouper fingerlings.